2011
DOI: 10.1186/1743-7075-8-32
|View full text |Cite
|
Sign up to set email alerts
|

Brazil nuts intake improves lipid profile, oxidative stress and microvascular function in obese adolescents: a randomized controlled trial

Abstract: BackgroundObesity is a chronic disease associated to an inflammatory process resulting in oxidative stress that leads to morpho-functional microvascular damage that could be improved by some dietary interventions. In this study, the intake of Brazil nuts (Bertholletia excelsa), composed of bioactive substances like selenium, α- e γ- tocopherol, folate and polyunsaturated fatty acids, have been investigated on antioxidant capacity, lipid and metabolic profiles and nutritive skin microcirculation in obese adoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 31 publications
(39 reference statements)
4
104
0
4
Order By: Relevance
“…In rodent experimental models, high-fat diets caused a decrease in capillary density. 25,33 In human studies, 15 to 25 g of brazil nuts per day for 16 weeks improved functional microvascular parameters such as red blood cell velocity in female obese subjects, 20 whereas 4 g of docosahexaenoic acid for 6 weeks improved forearm microcirculation in overweight, mildly hyperlipidemic men. 21 Our findings suggest that a dietary pattern of increased consumption of vegetable oils, poultry, and fish and seafood characterized by increased consumption of monounsaturated and polyunsaturated fatty acids and reduced consumption of saturated fatty acids (in the absence of high BP and insulin resistance) might represent an association with higher capillary density, thus less functional and structural capillary rarefaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rodent experimental models, high-fat diets caused a decrease in capillary density. 25,33 In human studies, 15 to 25 g of brazil nuts per day for 16 weeks improved functional microvascular parameters such as red blood cell velocity in female obese subjects, 20 whereas 4 g of docosahexaenoic acid for 6 weeks improved forearm microcirculation in overweight, mildly hyperlipidemic men. 21 Our findings suggest that a dietary pattern of increased consumption of vegetable oils, poultry, and fish and seafood characterized by increased consumption of monounsaturated and polyunsaturated fatty acids and reduced consumption of saturated fatty acids (in the absence of high BP and insulin resistance) might represent an association with higher capillary density, thus less functional and structural capillary rarefaction.…”
Section: Discussionmentioning
confidence: 99%
“…First, several nutrients and vasoactive dietary compounds have been described to affect the microcirculation, [20][21][22] as well as large artery function and structure. 23,24 Second, the role of nutrition in the development of insulin resistance, diabetes mellitus, and hypertension is already well described, [23][24][25][26] and it might be mediated by early alterations in the microcirculation.…”
Section: 1114 February 2014mentioning
confidence: 99%
“…Consumption of 26 g almonds/d or 36 g walnuts/d for 6 weeks led to a 19 % reduction in IL-6 with the almonds and 20 % reduction in TNF-a with the walnuts compared with baseline, but this did not reach significance. In addition, two studies with obese individuals demonstrated small but non-significant improvements in CRP (101) and IL-6 (60) with Brazil nut and mixed nut consumption, respectively. Suggested reasons for small but non-significant reductions in inflammatory markers were recruitment of healthy individuals who may only demonstrate limited improvements and diurnal effects of IL-6 that are more difficult to detect than other markers.…”
Section: Effects Of Nut Consumption On Inflammatory Markersmentioning
confidence: 99%
“…Suggested reasons for small but non-significant reductions in inflammatory markers were recruitment of healthy individuals who may only demonstrate limited improvements and diurnal effects of IL-6 that are more difficult to detect than other markers. One study with obese individuals demonstrated small but non-significant improvements in CRP (101) . Increased central adiposity and body weight are associated with increased CRP levels and adipose pro-inflammatory cytokines including IL-6 (102) .…”
Section: Effects Of Nut Consumption On Inflammatory Markersmentioning
confidence: 99%
“…Still regarding their influence on human metabolism, Cominetti et al (2012) demonstrated that obese people who consume Brazil nut daily could improve Se status and lipid profile, especially highdensity lipoprotein and cholesterol levels, thereby reducing cardiovascular risks. The consumption of 3 to 5 nuts a day for 16 weeks, improved the lipid profile and microvascular function in obese adolescents, possibly due to the high content of unsaturated fatty acids and bioactive substances (Maranhão et al, 2011). In addition, it was reported a long-term decrease in inflammatory markers after a single intake of Brazil nuts in healthy individuals (Colpo et al, 2014).…”
Section: Other Issuesmentioning
confidence: 99%